2007
DOI: 10.1109/tbme.2007.891934
|View full text |Cite
|
Sign up to set email alerts
|

Design of patient-specific gait modifications for knee osteoarthritis rehabilitation

Abstract: Gait modification is a nonsurgical approach for reducing the external knee adduction torque in patients with knee osteoarthritis (OA). The magnitude of the first adduction torque peak in particular is strongly associated with knee OA progression. While toeing out has been shown to reduce the second peak, no clinically realistic gait modifications have been identified that effectively reduce both peaks simultaneously. This study predicts novel patient-specific gait modifications that achieve this goal without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
164
3
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(205 citation statements)
references
References 30 publications
(38 reference statements)
6
164
3
5
Order By: Relevance
“…In agreement with this statement, aberrant knee joint loading has been identified as a factor affecting the progression of knee OA (13)(14)(15) in more advanced stages of OA (16): increased medial compartment loading has been associated with more pronounced clinical symptoms and OA severity as assessed by radiography (24,25). Most studies (17)(18)(19)(20)(21)(22)(23)(24) used the knee adduction moments (KAM), i.e. the external knee joint moment in the frontal plane was used as an indirect measure of medial compartment loading during functional activities.…”
Section: Introductionmentioning
confidence: 78%
“…In agreement with this statement, aberrant knee joint loading has been identified as a factor affecting the progression of knee OA (13)(14)(15) in more advanced stages of OA (16): increased medial compartment loading has been associated with more pronounced clinical symptoms and OA severity as assessed by radiography (24,25). Most studies (17)(18)(19)(20)(21)(22)(23)(24) used the knee adduction moments (KAM), i.e. the external knee joint moment in the frontal plane was used as an indirect measure of medial compartment loading during functional activities.…”
Section: Introductionmentioning
confidence: 78%
“…Second, clinicians should consider conservative interventions such as strengthening of the quadriceps 29,30 and iliotibial band 31,32 or gait retraining 33,34 to lower the adduction torque to below the target level. For example, a medial thrust gait motion designed in a recent computational study has been shown to reduce the peak adduction torque by 35-50%, 35 an amount comparable to HTO surgery, in the one patient studied thus far. To implement these suggestions, clinical gait labs would need to play a central role in initial screening, treatment design, and evaluation of treatment efficacy.…”
Section: Discussionmentioning
confidence: 96%
“…No RCTs were identified, and with the exception of 2 studies (26,27), none implemented modifications over the longer term. Studies lacked an adequate description of procedures, the modification implemented, the training methods, and the evaluation of skill acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies evaluated the overall or early-stance peak KAM (Table 2). Twelve studies reported early-stance peak KAM values (27,30 -33,35,43-46,48,49), with late-stance peak KAM values reported in 6 studies (27,30,32,33,35,45). Point estimates and measures of variability were not reported for 1 study and could not be extracted from graphical data (36).…”
Section: Reducing Medial Knee Load Using Gait Modificationsmentioning
confidence: 99%